Writing “A History of Ancient Israel”: In Dialogue with Christian Frevel - Edelman, Diana (Antiguo Oriente, 2024)
The English translation of the second edition of Christian Frevel’s Geschichte Israels was released in May, 2023. A panel discussion about the book took place at the Society of Biblical Literature 2024 Global Virtual Meeting, arranged by Dr. Juan Manuel Tebes. The following review article is an expansion and rearrangement of the comments I presented there, with a particular focus on what the subject of a history of ancient Israel could and should be and what the dating parameters for such a history could and should be.